2005
DOI: 10.2139/ssrn.702042
|View full text |Cite
|
Sign up to set email alerts
|

Business Groups and Tunneling: Evidence from Private Securities Offerings by Korean Chaebols

Abstract: Using a comprehensive sample of equity-linked private securities offerings by Korean firms from 1989 to 2000, we examine whether such offerings can be used as a mechanism for wealth transfer between issuers and acquirers. For deals involving issuers and acquirers in the same business group (chaebol), the announcement returns for chaebol-affiliated issuers with good past performance are lower than those for other types of issuers if the price discount is larger. In contrast, this deal leads to more value creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 22 publications
3
131
0
1
Order By: Relevance
“…This paper's bank perspective is also an extension of the literature on agency in business groups, which has emphasized agency conflicts between managers/controlling shareholders and minority shareholders, but less between debtholders and shareholders. This perspective reconciles the contradictory findings regarding Japanese business groups, as some studies found beneficial effects of business groups due to agency reduction (Hoshi et al, 1990;Prowse, 1990), while others found pernicious effects due to tunneling (Bae et al, 2002(Bae et al, , 2006Morck and Nakamura, 2005;Jiang et al, 2010). In the bank perspective, the former results are based on banks' heyday in Japan, when there were many opportunities for interests to align between banks and firms, while the latter results are based on banks' decline, when conflicts were more prevalent than alignments.…”
Section: Japan's Bank Index In Million Yensupporting
confidence: 65%
“…This paper's bank perspective is also an extension of the literature on agency in business groups, which has emphasized agency conflicts between managers/controlling shareholders and minority shareholders, but less between debtholders and shareholders. This perspective reconciles the contradictory findings regarding Japanese business groups, as some studies found beneficial effects of business groups due to agency reduction (Hoshi et al, 1990;Prowse, 1990), while others found pernicious effects due to tunneling (Bae et al, 2002(Bae et al, , 2006Morck and Nakamura, 2005;Jiang et al, 2010). In the bank perspective, the former results are based on banks' heyday in Japan, when there were many opportunities for interests to align between banks and firms, while the latter results are based on banks' decline, when conflicts were more prevalent than alignments.…”
Section: Japan's Bank Index In Million Yensupporting
confidence: 65%
“…Empirical analyses find that board size is positively related to the level of private benefits available to insiders in US firms (Boone et al, 2007). A large body of literature shows that group member firms are conducive to self-dealing transactions and that controlling families have strong incentives and enjoy plentiful channels to divert wealth from or between their member firms for their own private benefit (Johnson et al, 2000;Bae, Kang, and Kim, 2002;Bertrand, Mehta, and Mullainathan, 2002;Morck, Wolfenzon, and Yeung, 2005;Baek, Kang, and Lee, 2006;Cheung, Rau, and Stouraitis, 2006;among others). It is reasonable to conjecture that boards with larger size function more effectively to discourage controlling families from undertaking intragroup propping activities, which may harm the interests of minority shareholders of member firms from which resources are siphoned off.…”
Section: A Board Size and Intragroup Proppingmentioning
confidence: 99%
“…Johnson, La Porta, Lopez-de-Silanes, and Shleifer (2000) coin the term "tunneling" to describe the actual expropriation activities by controlling families and provide many examples of tunneling around the world. Atanasov (2005), Bae et al (2002), Bae, Baek, Kang and Liu (2012), Baek et al (2004), Baek, Kang, and Lee (2006), Bertrand et al (2002), Cheung, Rau, andStouraitis (2006), andJoh (2003) provide evidence of tunneling using data from Korea, India, Hong Kong, and Bulgaria. One common theme of these papers is that the control-ownership disparity is a good proxy for the risk of expropriation by controlling shareholders and that the disparity measure well captures the extent of actual expropriation, so that high control-ownership disparity is associated with poor firm performance and valuation.…”
Section: Risk Of Expropriation By Family Ownersmentioning
confidence: 98%
“…6. Numerous studies have documented evidence that the disparity between control and cash flow rights by controlling families is associated with greater expropriation risk and thus poor firm performance (Atanasov, 2005;Bae et al, 2002Bae et al, , 2012Baek et al, 2004Baek et al, , 2006Bertrand et al, 2002;Cheung et al, 2006;Claessens et al, 2000Claessens et al, , 2002Joh, 2003;La Porta et al, 2002;Lemmon & Lins, 2003;Mitton, 2002). 7.…”
Section: Notesmentioning
confidence: 99%